The Circular Economy of E-Waste in the Netherlands: Optimizing Material Recycling and Energy Recovery - Laura Golsteijn; Elsa Valencia Martinez (Journal of Engineering)
In the Netherlands, waste electric and electronic equipment (e-waste) is an important point for discussion on the circular economy agenda. This paper shows the Dutch example of how “waste” can be turned into a resource, and the climate change benefits from appropriate collection and recycling. It describes the avoided emissions of CO2-equivalents due to e-waste recycling and appropriate removal and destruction of (H)CFCs contained in cooling and freezing appliances. Six different e-waste categories were included, and the results of 2016 were compared to previous years (2009–2015). In 2016, 110,000 tonnes of e-waste were collected. 80% of this was recycled to useful materials. Additionally, it resulted in 17% energy recovery. That year, the recycling of e-waste and the removal of (H)CFKs resulted in approximately 416,000 tonnes of avoided emissions of CO2-equivalents. Although the phasing out of cooling and freezing appliances with (H)CFKs led to a general decrease in the quantity of avoided CO2 emissions over time, removal of (H)CFKs still explained most of the avoided CO2 emissions. Material recycling appeared particularly beneficial for cooling and freezing appliances and small and large household appliances. The paper ends with reasons to further close the loop and ways forward to do so.